Dziesięciu największych oszustów XXI wieku - Kropiwnicki, Jerzy (Annales. Etyka w Życiu Gospodarczym, 2013)
Non-ethical behaviour of persons belonging to financial elites of the world has been characteristic of our times. They could be found in many countries – from the USA to France, Japan, China, etc. Their activities have financially ruined many people and caused enormous losses to the institutions they have been working for. Their motives have been simple and obvious – greed with no moral reservations. However, greed has also been evident in those naive people who have chosen to believe the swindlers and entrust their money. Moreover, greed has motivated the management of prominent companies, who seemed to tolerate evidently illegal but profitable activities. This paper presents the specific careers of the 10 biggest swindlers: Bernard Madoff, Allen Stanford, Jérôme Kerviel, Ramalinga Raju, Nevin Shapiro, Stein Bagger, Wu Ying, Kevin Foster, Hannu Kailajärvi and Kenneth J. Starr. The 11th person mentioned at the very beginning of the paper isCharles Ponzi, the infamous inventor of the “Ponzi Pyramid”.